Associations between cardiovascular disease and its risk factors with hearing loss—A cross‐sectional analysis. (9th August 2017) - Tan, H.E.; Lan, N.S.R.; Knuiman, M.W.; Divitini, M.L.; Swanepoel, D.W.; Hunter, M.; Brennan‐Jones, C.G.; Hung, J.; Eikelboom, R.H.; Santa Maria, P.L.
Abstract : Objectives: To investigate the relationship between hearing loss and cardiovascular disease risk factors. Design: Cross‐sectional study. Methods: Participants were recruited between May 2010 and December 2015 and answered a health and risk factor questionnaire. Physical and biochemical assessments were performed. Setting: A community‐based population. Participants: A total of 5107 participants born within the years 1946‐1964 enrolled in the Busselton Healthy Ageing Study. Main outcome measures: Hearing was assessed behaviourally through the best ear pure‐tone average (500, 1000, 2000, 4000 Hz), low‐frequency average (250, 500, 1000 Hz) and high‐frequency average (4000, 8000 Hz). Self‐reported hearing loss, tinnitus and hyperacusis were assessed via questionnaire. Cardiovascular risk factors were assessed via a patient‐completed questionnaire and objective measurements including blood pressure, body mass index, waist circumference, lipid profile and glycated haemoglobin. Results: Of the participants, 54% were female, with the mean age of 58 years (range 45‐69 years). Age, sex and family history of hearing loss were consistently strong determinants of hearing loss outcomes. After adjusting for these, obesity, current smoking, peripheral arterial disease and history of cardiovascular disease were significantly associated with pure‐tone, low‐frequency and high‐frequency hearing loss. In addition, high blood pressure, triglyceride and glycated haemoglobin were significantly associated with low‐frequency hearing loss. There was a graded association between hearing loss and Framingham Risk Score for cardiovascular risk ( P <0.001). Conclusions: Established cardiovascular disease and individual and combined cardiovascular disease risk factors were found to be associated with hearing loss. Future research should prospectively investigate whether targeting cardiovascular disease can prevent hearing loss.